Skip to main content

Questions tagged [conjunctive-normal-form]

A formula is in conjunctive normal form (CNF) if it is a conjunction of clauses, where a clause is a disjunction of literals.

1 vote
1 answer
601 views

Convert $A⟺B⟺C$ into Conjunctive Normal Form.

Eliminate implications and bi-conditionals using formulas: $A⟺B⟺C$ Attempt: $≡ (A⟹B)∧(B⟹A)⟺C$ $≡ (((A⟹B)∧(B⟹A))⟹C)∧(C⟹((A⟹B)∧(B⟹A)))$ $≡ ¬((A⟹B)∧(B⟹A))∨C ∧ ¬C∨((A⟹B)∧(B⟹A))$ $≡ ¬((¬A∨B)∧(¬B∨A))∨C ...
DEC NAST's user avatar
2 votes
2 answers
455 views

Converting to conjunctive normal form?

How to convert to conjunctive normal form? If i have a formula: $(\neg Q\land P) \lor (\neg Q\land R) \lor (Q \land \neg P \land \neg R) \lor (\neg P \land \neg R)$ The formula is in disjunctive ...
miamiamia's user avatar
0 votes
1 answer
41 views

How many subsets of size $n$ in $S=\{x_1,\dots ,x_{2n}\}$ under restrictions

Let $S=\{x_1,\dots ,x_{2n}\}$. How many subsets of size $n$ are in $S$ such that $\forall1\le i\le n: x_i$ and $x_{n+i}$ are not in the same set. I ran into this problem when thinking how many ...
BulGali's user avatar
  • 375
2 votes
0 answers
44 views

I don't know that this solution is right

I have the statement ∃xP(x) ↔ ∃xQ(x) and I have to write it in prenex normal form. First I rewrote it as two conditionals: ∃xP(x) ↔ ∃xQ(x) ≡(∃xP(x) → ∃xQ(x))∧ (∃xQ(x) → ∃xP(x)) Then I renamed the ...
Lee's user avatar
  • 21
2 votes
2 answers
375 views

Why Does Order of Negation Matter in First Order Logic Resolution?

Consider the situation in which we have $f(A)$ as a given and are attempting to show that $\exists x f(x)$. Using resolution, we negate the conclusion, convert everything to CNF, and attempt to ...
quixotrykd's user avatar
6 votes
2 answers
7k views

How to compute CNF from truth table

How can I write a propositional formula with variables p, q, r in a CNF that has 3 models v1, v2, v3: I've failed to find any related sources.
saidfagan's user avatar
  • 163
1 vote
1 answer
136 views

Is Predicate Resolution the Only Way To Reduce The Size CNF Clauses?

I have a CNF formula like $(x_1∨x_2∨x_3') ∧ (x_1' ∨ x_4 ∨ x_2)$ ... Perhaps I want to see if the equation is equivalent to a CNF equation containing a single literal ($x_2$ for example). I already ...
ian.p.swift's user avatar
1 vote
3 answers
48 views

How to convert (F⇒(H⇒G))⇒(F⇒(G⇒H)) to Conjunctive Normal Form?

I've expanded the formula to: $$(F \wedge H \wedge\neg G) \vee (\neg F \vee\neg G \vee H)$$ but don't know how to switch the first set to or and the middle or to an and.
Phalanx's user avatar
  • 21
0 votes
2 answers
106 views

What paper proved the completeness of Ordered Resolution?

I am having trouble finding online the original proof of the completeness of Ordered Resolution. Does anyone happen to know where it exists? Thanks!
user1050268's user avatar
0 votes
1 answer
316 views

How to convert this formula to CNF

I have the following formula and want to turn it into CNF without creating a truth table: ~((X -> ~(Y or Z)) and ((X and Y) or ~Z)) I was doing the following ...
TmCrafz's user avatar
1 vote
2 answers
155 views

Constructive proof layers-norm (propositional logic)

I have to write a constructive proof that for every propositional formula has an equivalent formula in Layers-Norm We define Layer-Norm for propositional formulas as follows: Literals are in Layer-...
Rapiz's user avatar
  • 115
0 votes
1 answer
126 views

Task about Conjunctive and Disjunctive normal form.

Happy new year to all! I have a question related to my Discrete Mathematics examination: Consider the following (parametrized) propositional formula $𝜑_𝑛$: ($p_1$V$p_{2n+1}$) & (!$p_1$V!$p_2$)...
pupsemerdi's user avatar
1 vote
1 answer
473 views

Simplifying boolean expression to minimum CNF

I have the boolean expression, $$(a\not\to b)\lor(c\not\to d)\lor(a\not\to d)\lor(b\not\to d)$$ Can I simplify this to, $$ (a \vee c \vee b ) \wedge (a \vee \neg d) \wedge (\neg b \vee \neg d) $$ ...
Jude Molloy's user avatar
0 votes
1 answer
665 views

Converting to DNF from CNF

I'm having a bit of a problem when trying to convert this CNF formula to DNF: \begin{align} & \left(a_1 \vee \neg a_2 \vee \neg a_3 \vee ... \vee \neg a_K \right) \wedge \\ & \left(\neg a_1 \...
Gogol31's user avatar
0 votes
1 answer
213 views

CNF simplification

I would like to know if it is possible to simplify the CNF equation. I have this equation - $$ (x_{1} \lor x_2 \lor \lnot x_3 \lor \lnot x_4) \land (x_1 \lor \lnot x_2 \lor x_3 \lor \lnot x_4) \land (...
Raicha's user avatar
  • 3

15 30 50 per page
1
4 5
6
7 8
14